The Effect of Corporate Social Responsibility Commitment and Marketing Communication on Banking Marketing Performance in the Metropolitan City of Bandung - Rizka Aula Assaf (International Journal of Education, Information Technology, and Others, 2023)
The banking industry has not been effective in implementing marketing communications and corporate social responsibility programs. Likewise marketing performance has not been achieved as expected. This research was conducted in the banking industry in the city of Bandung with a sample of 38 banking industries which were taken using a random sampling method. The analysis procedure uses Structural Equation Modeling based on Partial Least Square. This research produces a new model that is different from previous research where marketing communication programs do not directly affect the marketing performance of the banking industry. in conclusion